Optimization of Total Phenolic Content Analysis of Chayote (Sechium edule) using Ultrasonic-Assisted Extraction and Response Surface Methodology - Syahfa Adinda Relyando; Ayu Wulandari; Ditta Kharisma Yolanda Putri; Bekti Palupi; Istiqomah Rahmawati (JOBC, 2023)
Chayote (Sechium edule) is a plant from the Cucurbitaceae family that contains several vitamins, such as A, B, and C, and is often used for medicinal purposes. Based on phytochemical analysis, chayote extract contains bioactive compounds like phenolics. Phenolic compounds are secondary metabolites used as cosmetic and medicinal ingredients due to their ability to reduce oxidative stress. This research uses UV-Vis spectrophotometry to determine the chayote extract's total phenolic content and antioxidant activity. Chayote extract was obtained using the Ultrasonic Assisted-Extraction (UAE) method with 96% ethanol solvent. The extraction variables used were time (15, 20, and 25 minutes), amplitude (45, 65, and 85%), and solvent ratio (1:5, 1:10, and 1:15). The determination of total phenolic content was based on the Folin-Ciocalteau method. At the same time, antioxidant activity was determined using DPPH. Determining chayote extraction parameters for total phenolic content using the Response Surface Methodology with a Box-Behnken type. The optimal conditions for chayote extraction were 1.327 mg GAE/g sample for total phenolic content and 29.45% for antioxidant activity under 20 minutes of extraction time, 65% amplitude, and a 1:10 solvent ratio.